Effectiveness of Gluteus Maximus Activation in Correcting Pelvic Tilt for People with Mechanical Low Back Pain (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Low back pain (LBP) is one of the most common conditions in industrialized modern societies.Low back pain is usually nonspecific or mechanical. People with LBP have previously been found to have poorendurance and delayed Gluteus Maximus muscle firing. Anterior pelvic tilt was also believed to cause pelvicgirdle discomfort and generalized LBP.Purpose: To evaluate the effectiveness of Gluteus Maximus Activation in correcting anterior pelvic tilt, reducingpain and improving the Functional Outcome among Mechanical Low back pain subjects.Materials and Methods: About 250 participants were selected from Thiraviam Orthopaedic Hospital by usingKinovea software based on inclusion and exclusion criteria. They were divided into 2 groups, Experimental Group(n=125), Control Group (n=125). Both groups were given stretching exercises then Experimental group was givenGluteus Maximus activation exercise with IFT and Control group was given spinal stabilization exercise with IFT.Interventions were given 5 times a week for 6 weeks. Study period : October 2022 to July 2023.Results: Pre-test and post-test values were analyzed and the result suggests that GM Activation Group hassignificant improvement when compared with Spinal stabilization Group with P
Keywords: Mechanical Low Back Pain, Pelvic Tilt, Kinovea software, Roland Morris Disability Questionnaire, Spinal stabilization, Gluteus Maximus Activation